Intracranial Pathology (CT+) in Emergency Department Patients With High GCS and High Standard Assessment of Concussion (SAC) Scores. Issue 3 (May 2018) - Curley, Kenneth C.; O'Neil, Brian J.; Naunheim, Rosanne; Wright, David W.
Abstract : Objective: To demonstrate that a subpopulation of patients with mild/moderate traumatic brain injury (TBI) had intracranial pathology despite having a Glasgow Coma Scale (GCS) score of 15 and a Standardized Assessment of Concussion (SAC) score of 25 or higher. Setting: A network of 11 US emergency departments (ED) enrolling patients in a multisite study of TBI. Participants: Men and women between the ages of 18 and 85 years admitted to a participating ED having sustained a closed head injury within the prior 72 hours and a GCS score of 13 to 15 at the time of enrollment. Design: Prospective observational study. Main Measures: GCS, SAC, computed tomography (CT) positive or negative for intracranial pathology, Marshall scoring of CT scans. Results: Of 191 patients with intracranial pathology (CT+) and having a SAC score recorded, 24% (46/191) had a SAC score in the normal range (≥25) as well as a GCS score of 15. All causes of CT+ brain injury were present in both SAC groups. Conclusion: A normal GCS score and a SAC score do not exclude the possibility of significant intracranial injury.